KEARIFAN LOKAL MASYARAKAT PADA PENGELOLAAN AGROFORESTRI DI DESA BATU NINDAN KABUPATEN KAPUAS - Cahyani Hanifah; Hafizianor Hafizianor; Asysyifa Asysyifa (Universitas Lambung Mangkurat, 2023)
Local wisdom is a form of behavior or mindset of the people of an area that is applied in the environment where they live. The purpose of this study was to examine the local wisdom of the community in managing agroforestry land in Batu Nindan Village. This research method is interviewing key respondent (such as village heads, community leaders, and agroforestry farmers) who have information related to the problem under study regarding forms of local community wisdom in managing agroforestry land. The interview method used is in-depth interviews to key respondent. The data were obtained from direct observations in the field. The results of the observation of this study are that there are three components, namely Ideological Superstructure (relating to the carrying out of a traditional ritual during land clearing called the ritual